Penerapan metode 7S McKinsey pada Ebay sebagai Strategi E-commerce & Bonus Demography Menghadapi Globalisasi - Hasna Widya Pratiwi; Fuad Mas'ud (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
E-commerce is an important pillar in the changing times and gives a significant influence on everyday human life. E-bay which is one of the largest e-commerce companies in the world has grown very rapidly and provides exceptional service to the world community. The services provided have helped a lot in overcoming problems in facing demographic bonuses, especially absorbing labor; human resource development and information technology development. The strategy used by ebay.com also has a tremendous impact on competitors in the field of e-commerce, a strategy owned by ebay.com despite being very good, still requires innovation in it, this should be done because very fast and inflexible changes in e-commerce strategies, ebay will not be able to cope with those changes. change is a good form, where this transformation can have a positive impact on society and make changes to culture significantly, the change should cover the whole lifestyle and also cover the whole mindset and attitude, therefore ebay.com make many changes positive in the face of globalization, and changes in e-commerce strategy in the face of competition among companies in the world, especially in the field of e-commerce and human resources